1984
DOI: 10.1073/pnas.81.19.6004
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-specific cDNAs from mammalian cells temperature sensitive for growth.

Abstract: A library of double-stranded cDNA was constructed from ts13 cells, a Gl-specific temperature-sensitive hamster cell line. The cDNAs, cloned into pBR322, were prepared from poly(A)+ mRNA isolated from ts13 cells 6 hr after serum stimulation at the permissive temperature of 34°C.Differential screening of the library with G -specific and Gospecific single-stranded cDNA probes prepared from the same cells identified five cDNA clones whose sequences were preferentially expressed in G1. (2), is a mutant of RNA poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
1
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 43 publications
5
135
1
1
Order By: Relevance
“…tsAF8 cells are G1-specific, temperature-sensitive mutants originally isolated from BHK cells (12); these cells have been extensively characterized (3,12,25 Berger (9). Plasmid DNA was isolated and purified by phenol extraction and Sepharose 2B chromatography (31,32,44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…tsAF8 cells are G1-specific, temperature-sensitive mutants originally isolated from BHK cells (12); these cells have been extensively characterized (3,12,25 Berger (9). Plasmid DNA was isolated and purified by phenol extraction and Sepharose 2B chromatography (31,32,44).…”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation and blot procedures were previously described (31). Briefly, after extraction RNA was denatured and size fractionated on 1% agarose gels containing 6.6% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for these important mammalian "cell division cycle" genes (5) has been carried out in a number of laboratories using differential colony hybridization screening of cDNA libraries with radiolabelled cDNA probes that reflect the quiescent and stimulated growth states (e._&. [5][6][7][8][9][10]. These and other studies have uncovered so far some forty or so genes only a few of which share identity with characterized oncogenes (reviewed in 11).…”
Section: Introductionmentioning
confidence: 99%
“…Although the function of calcyclin is still unknown, several observations can be made: the calcyclin gene was induced by serum, platelet-derived growth factor, or epidermal growth factor [1,4,5]. The gene product was shown to bind both zinc and calcium [6] which indicated that it is involved in processes related to signal transduction.…”
mentioning
confidence: 99%